The impact of the program note your money worth over collection of the state of ICMS CearÃ - Maria Iara Henrique PalÃcio (2012)
This paper analyzes the impact of the program Your Money Note Valley, on the collection of ICMS of the State of Ceara from an analysis of the collection of the Retail Sector before and after the entry into force of that program, using the Chow test to examine whether the time series of Revenue Tribute in Ceara shows a structural change. Created in December 2004 (Law 13,508) by the Finance Secretary of the State of Ceara, The Program Your Money Note Valley aimed at combating tax evasion and encourages citizens and businesses to conduct transactions with the use of the invoice. The work makes reference to improving the tax authorities of tax revenue efficiency due to the Education Fiscal and Fiscal Policies to Combat Tax Evasion and Evasion. It is noteworthy the role and interest of the democratic rule of law in the regulatory process and collection of taxes to meet the social demands Increase the stock of economic capital, social and human through the exercise of citizenship and social responsibility shared between state and citizens to improve the training of effective improvement tax collection and enforcement authority of public resources and social control. The results show that there is a structural break in month / year, indicating that the mentioned program is producing the desired results in terms of increased revenue and consequent awareness of Cearaâs citizens.